2023
DOI: 10.1136/bmjopen-2022-071165
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with first antenatal care (ANC) attendance within 12 weeks of pregnancy among women in Lira City, Northern Uganda: a facility-based cross-sectional study

Walter Acup,
Marc Sam Opollo,
Betty Nancy Akullo
et al.

Abstract: ObjectiveThis study aimed at assessing factors associated with first antenatal care (ANC) attendance within 12 weeks of pregnancy among women in Lira City.DesignA cross-sectional study.SettingsThe study was conducted in health facilities offering ANC services in Lira City, Northern Uganda.ParticipantsThe study was among 368 pregnant mothers attending their first ANC in the three selected facilities (Lira Regional Referral Hospital, Ober Health Center IV and Pentecostal Assembly of God Mission Health Center IV)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Adjusted odds ratio showed that the likelihood of early initiation of ANC was four times higher in married women compared to unmarried ones. This finding concurs with a study other studies that have established that unmarried women were unlikely to start ANC early (14,15,18,19). This may be due to the support that married women get from their partners unlike the unmarried who may hide their pregnancy because of fear of embarrassment (18,22) This study determined that woman's occupation determine ANC booking.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Adjusted odds ratio showed that the likelihood of early initiation of ANC was four times higher in married women compared to unmarried ones. This finding concurs with a study other studies that have established that unmarried women were unlikely to start ANC early (14,15,18,19). This may be due to the support that married women get from their partners unlike the unmarried who may hide their pregnancy because of fear of embarrassment (18,22) This study determined that woman's occupation determine ANC booking.…”
Section: Discussionsupporting
confidence: 90%
“…This may be due to women's lack of awareness regarding the importance of early initiation of ANC and the attitude that the woman will make numerous visit before delivery if ANC is started early. The proportion of the women who stated ANC within the recommended period in this study was slightly higher that in several other studies (12,19,20), but similar to a finding by Acup et al (15) In this study, maternal age was found to be associated with early initiation of ANC. Women aged 20-24 years are five times more likely to book ANC early compared to other age groups.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A recent study conducted in Papua New Guinea revealed the prevalence of early ANC intention is 23% 10 . According to studies done in Uganda, the proportion of early ANC visit was 36% 11 . Likewise, another study conducted in Northwest Ethiopia reported that 52% of women booked their first ANC visit after 4 months of pregnancy 12 .…”
Section: Introductionmentioning
confidence: 99%